UMP feted 165 asnaf family members and distributed raya goodies - UMP, PNC (Pejabat Naib Canselor, 2016)
A total of 165 people who were under the asnaf category and living in Kuantan and Pekan were feted in an iftar programme organised by Universiti Malaysia Pahang (UMP), together with UMP Women Association (Matahari) and UMP Advanced Education (UAE).